The effect of 12 weeks of combined upper- and lower-body high-intensity interval training on muscular and cardiorespiratory fitness in older adults - Hurst, Christopher (Aging Clin Exp Res, 2018)
BACKGROUND: High-intensity interval training (HIT) can impact cardiorespiratory and muscular fitness simultaneously, yet protocols typically focus on lower-body exercise. For older adults however, performing activities of daily living requires upper- and lower-body fitness. AIMS: To assess the effects of combined upper- and lower-body HIT on fitness in adults aged > 50 years. METHODS: Thirty-six adults (50–81 years; 21 male) were assigned via minimisation to either HIT (n = 18) or a no-exercise control group (CON, n = 18) following baseline assessment of leg extensor muscle power, handgrip strength, cardiorespiratory fitness (predicted VO(2max)) and health-related quality of life (HRQoL). The HIT group completed two training sessions per week for 12-weeks, performing a combination of upper-, lower- and full-body exercises using a novel hydraulic resistance ergometer. Data were analysed via ANCOVA with probabilistic inferences made about the clinical relevance of observed effects. RESULTS: All participants completed the intervention with mean (82 ± 6%HR(max)) and peak (89 ± 6%HR(max)) exercise heart rates confirming a high-intensity training stimulus. Compared with CON, HIT showed possibly small beneficial effects for dominant leg power (10.5%; 90% confidence interval 2.4–19.4%), non-dominant leg power (9.4%; 3.3–16.0%) and non-dominant handgrip strength (6.3%; 1.2–11.5%) while the intervention effect was likely trivial (5.9%; 0.5–11.5%) for dominant handgrip strength. There was a likely small beneficial effect for predicted VO(2max) (8.4%; 1.8–15.4%) and small-moderate improvements across several domains of HRQoL. CONCLUSION: Combined upper- and lower-body HIT has small clinically relevant beneficial effects on muscular and cardiorespiratory fitness in older adults. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40520-018-1015-9) contains supplementary material, which is available to authorized users.